Functional strength training and its impact on some of the skill abilities of soccer players - Ibrahim, Mohammed (Journal of Physical Education, 2025)
The researcher touched on the importance and place of the game of football among sports, as functional strength exercises were prepared and their impact on some skill abilities in football. The research community included the teams of government institutions in Diyala Governorate, and the research sample was chosen intentionally, which was represented by the Diyala youth and adult football teams. There are 9 indoor players This research is one of the scientific attempts to raise the skill level of the teams of government institutions in the governorate through the use of functional strength training. The results showed that there is a clear development among the research sample in the post-test as a result of the use of these training